Survey of Private Sector Trade Credit Developments. (Policy Papers; Policy Paper ;, 2009)
In response to the dearth of information on trade finance, the Fund has undertaken a survey of major advanced country and emerging market banks. The results suggest that the cost of trade finance is rising globally, but that provision is falling in emerging markets while staying stable in advanced countries, possibly reflecting structural differences in markets.